Transformational Leadership, Soft HR Approach, and Millennial Workforce Engagement in International NGOs in Nairobi, Kenya - Mburu, Lucas N.; Ragui, Dr. Mary, PhD; Ongeti, Dr. Walter, PhD (INTERNATIONAL JOURNAL OF RESEARCH AND INNOVATION IN SOCIAL SCIENCE (IJRISS), 2024)
Engagement of the Millennial Workforce is a significant focus within the workplace. Their shared values and attitudes, influenced by similar social and economic circumstances, are of ongoing scholarly interest. Extant research indicates concerning levels of disengagement among Millennials in the workforce, with many open to new job opportunities due to intolerance for conflicts and ambiguity, despite demonstrating the ability to delve deep into issues. The current study aimed to investigate the issue of Millennial Workforce engagement within Kenya’s international non-governmental organization (INGO) sector as a leadership issue by examining the interaction between transformational leadership, soft HR management, and Millennial Workforce engagement. The study was anchored on McGregor’s Theory Y. The research was a cross-sectional survey involving a purposive sample of 384 Millennials drawn from 32 selected INGOs with physical presence in Nairobi. Data was collected using Multifactor Leadership Questionnaire, researcher-developed Soft HR scale, and the Utrecht Work Engagement Scale. The data was subjected to mediator analysis following a four-step process using the Statistical Package for the Social Sciences. The analysis demonstrated partial mediation, thus confirming the role of a soft HR approach as an intermediary in the connection between leadership and engagement. Creating a workplace environment that values Millennial’s input and participation is essential for driving their engagement. By providing forums for expression, listening to and acting on feedback, and involving them in decision-making processes, organizations can cultivate a culture of inclusivity, trust, and collaboration that keeps them highly engaged.